Improving care of chronic conditions for women veterans: identifying opportunities for comparative effectiveness research. (March 2014) - Bielawski, Mark P; Goldstein, Karen M; Mattocks, Kristin M; Bean-Mayberry, Bevanne; Yano, Elizabeth M; Bastian, Lori A
This article aims to critically analyze research focused on the findings for five chronic conditions: chronic pain, diabetes, cardiovascular disease, HIV and cancer among women veterans to identify opportunities for comparative effectiveness research. We provide a descriptive analysis from the relevant articles in prior systematic reviews. In order to identify potential gaps in research for these specific conditions, we also conducted a literature search to highlight studies focusing on women veterans published since the last systematic review. While the scientific knowledge base has grown for these chronic conditions among women veterans, the vast majority of the published literature remains descriptive and/or observational, with only a few studies examining gender differences and even fewer clinical trials. There is a need to conduct comparative effectiveness research on chronic conditions among women veterans to improve health and healthcare.